Increased APRIL Expression Induces IgA1 Aberrant Glycosylation in IgA Nephropathy. Issue 11 (March 2016) - Zhai, Ya-Ling; Zhu, Li; Shi, Su-Fang; Liu, Li-Jun; Lv, Ji-Cheng; Zhang, Hong
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Aberrant glycosylated IgA1 molecules, mainly galactose-deficient IgA1 (Gd-IgA1), are important causal factors in IgA nephropathy; however, the underlying mechanism for the production of aberrantly glycosylated IgA1 is unknown. A recent genome-wide association study identified a novel IgAN susceptibility gene, TNFSF13, which encoded a proliferation-inducing ligand (APRIL) that promotes lymphocyte proliferation and IgA class switching. We aimed to explore the mechanism of APRIL's involvement in IgAN. We enrolled 166 patients with IgAN and 77 healthy controls and detected the plasma APRIL levels by the ELISA method, identified the mRNA expression of APRIL and its receptors by relative quantitative PCR, and confirmed by in vitro experiment. We identified increased plasma APRIL levels in IgAN, which was further proved by upregulated mRNA expression in B-lymphocytes from 27 IgAN patients. Analysis of the clinical characteristics of patients with IgAN showed that higher plasma APRIL level was associated with more severe clinical presentations (high proteinuria and low eGFR). The plasma APRIL level was positively correlated with Gd-IgA1 levels. Furthermore, exogenous APRIL could induce more production of Gd-IgA1 in cultured lymphocytes from patients with IgAN, compared with that from healthy controls. And, the relative higher expression of receptors of APRIL, that is, BCMA and TACI, in B-lymphocytes from IgAN patients were observed. Our findings implied that in patients with IgAN, increased APRIL is accompanied elevated expression of its receptors in B-lymphocytes, which induces overproduction of Gd-IgA1, ultimately contributing to the pathogenesis of IgAN.